Profile of Hazardous and Toxic Materials Storage in the Hazardous and Toxic Materials Warehouse of Blambangan Regional Public Hospital Banyuwangi - Dita Amanda Deviani; Stephanie Devi Artemisia; Anung Kustriyani; Indah Ayu Lestari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Hazardous and Toxic Materials are substances, chemical and biological in a single form or mixture, whose properties, concentration, or amount can contaminate, damage, and endanger the environment and health directly or indirectly. Improper storage of Hazardous and Toxic Materials can harm humans and the environment. Blambangan Regional Public Hospital has a Hazardous and Toxic Materials Warehouse used for storing chemicals needed for pharmacy service processes. This study aimed to investigate the Hazardous and Toxic Materials storage in the Hazardous and Toxic Materials Warehouse at Blambangan Regional Public Hospital. This was an observational study using descriptive methods. It was conducted in the Hazardous and Toxic Materials Warehouse of Blambangan Regional Public Hospital during June-July 2023. The results showed that the Hazardous and Toxic Materials storage in the Blambangan Regional Public Hospital Warehouse had Hazardous and Toxic Materials inventory data, and Material Safety Data Sheets (MSDS). The availability of Hazardous and Toxic Materials safety facilities includes Personal Protective Equipment (PPE), Hazardous and Toxic Materials signs and symbols, and a spill kit. However, the lack of safety facilities includes Hazardous and Toxic Materials cabinets, body wash stations, and eye wash stations. Guidelines and Standard Operating Procedures (SOPs) for Hazardous and Toxic Materials management are still incomplete, and Hazardous and Toxic Materials emergency handling is not yet well established. This study concludes that the Hazardous and Toxic Materials storage in Blambangan Regional Public Hospital Warehouse does not meet the requirements according to Permenkes No. 66 of 2016, because out of 5 required aspects, only 3 aspects are fulfilled.